Obstacles to implementing the Kulliyatul Mu’allimin Al-Islamiyah curriculum in Arabic at the Al Furqon Islamic Boarding School - Muhammad Fadhil Husein; Hanan Riswar; Muhajir Muhajir; Ade Satria Fauzi Nasution (AL-TARBIYAH: Jurnal Pendidikan (The Educational Journal), 2024)
This study aims to evaluate the implementation of the Kulliyatul Mu'allimin Al-Islamiyah (KMI) Curriculum in Arabic language learning at Pondok Modern Al-Furqon, and to identify the challenges and solutions faced in the process. The research method used is qualitative with a case study approach, involving interviews with the KMI director, teachers, and students, as well as direct observation of the learning process and analysis of documents related to the curriculum. The results of the study indicate that the implementation of the KMI curriculum at Pondok Modern Al-Furqon has only reached 70% with Arabic language learning taking place for 24 hours through formal and non-formal approaches. This study identified various obstacles in the implementation of the KMI curriculum at Pondok Modern Al-Furqon, including the use of two curricula, namely the KMI curriculum and the national curriculum, the tight schedule of activities, and the limited understanding of teachers regarding the curriculum due to differences in educational backgrounds. To overcome these obstacles, Pondok Modern Al-Furqon conducted weekly and monthly evaluations, and provided training to teachers on the implementation of the KMI curriculum. This study concludes that despite challenges in implementing the curriculum, the efforts made by the pesantren show a commitment to improving the quality of Arabic language learning and the development of the character of the students. These findings are expected to contribute to the development of the curriculum in other pesantren and improve the effectiveness of Arabic language learning in Indonesia.